2021
DOI: 10.3390/su132313491
|View full text |Cite
|
Sign up to set email alerts
|

Humidification-Dehumidification Desalination System Powered by Simultaneous Air-Water Solar Heater

Abstract: A humidification–dehumidification (HDH) desalination system requires thermal energy to desalt seawater. An environmentally friendly approach to obtain thermal energy is to utilize solar energy using solar collectors. Either seawater or air (or both) are typically preheated by HDH desalination systems before these fluids are conveyed to the humidifier column. Compared with preheating only air or water, preheating both is preferred because improved performance and higher productivity are achieved. Many researche… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…In the last few years, desalination techniques employing solar radiation have been receiving attention from researchers because of their cost-effectiveness and easy application [15][16][17]. Various types of solar desalination systems (SDSs) have been designed and investigated in the past few years [18,19]. Basically, SDSs capture water evaporation from the basin, which condenses on the transparent cover above the system.…”
Section: Introductionmentioning
confidence: 99%
“…In the last few years, desalination techniques employing solar radiation have been receiving attention from researchers because of their cost-effectiveness and easy application [15][16][17]. Various types of solar desalination systems (SDSs) have been designed and investigated in the past few years [18,19]. Basically, SDSs capture water evaporation from the basin, which condenses on the transparent cover above the system.…”
Section: Introductionmentioning
confidence: 99%
“…A desalination system with humidification and dehumidification (HDH) requires heat to carry out the process of seawater desalination [2]. An effective and environmentally friendly approach to obtain heat energy is the use of solar energy using solar air heaters.…”
Section: Introductionmentioning
confidence: 99%
“…Keywords presented are selected to better represent the analyzed domain 2. The table colors represent the keyword creation networks shown above in Figure8.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In a study conducted by Orfi et al [5], it was concluded that the water output is directly proportional to radiation intensity. Soomro et al [6] showed that higher water output and GOR in their proposed HDH system belonged to the months in which the radiation intensity was greater. Considering the crucial importance of sunlight in the operation of HDH systems, there have been multiple kinds of research regarding the operation of HDH systems in unsuitable climates.…”
mentioning
confidence: 99%